2018
DOI: 10.1002/adfm.201807688
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Charge Carrier Chemistry in Lithium Sulfide

Abstract: Lithium sulfide is a functional material of great importance for battery research, since it is the discharge product in Li–S cathodes and a frequent component of anode passivation layers. In both cases, transport of charge carriers in Li2S is critical for performance. The exploration of charge carrier chemistry in such a simple binary compound is also of fundamental scientific interest. For that purpose, impedance spectroscopy and electromotive force measurements are performed over a broad range of temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 47 publications
4
62
0
Order By: Relevance
“…[42] The nanostructure rendered good contact between the Li 2 S and the carbon matrix as well as an adequate Reproduced with permission. [27] Copyright 2019, Wiley-VCH. density of reaction sites.…”
Section: The High Overpotential Voltage In the Initial Charge Processmentioning
confidence: 99%
“…[42] The nanostructure rendered good contact between the Li 2 S and the carbon matrix as well as an adequate Reproduced with permission. [27] Copyright 2019, Wiley-VCH. density of reaction sites.…”
Section: The High Overpotential Voltage In the Initial Charge Processmentioning
confidence: 99%
“…Therefore, the effect of a MgS particle should be noted in this case as the effect of nanoionics was expected to contribute to an improvement of both the ionic conductivities and activation energy for the samples with x = 0.15 and 0.2. Upon doping with 4% mol of MgS, a slight increase of the ionic conductivity of Li 2 S was observed by Lorger et al [12]. Recently, nanocomposites of Li 2 S and transition metals were prepared by heating mixtures of Li metal and transition metal sulfides at 600 °C [20].…”
Section: Methodsmentioning
confidence: 93%
“…This observation may suggest that Mg 2+ was successfully dissolved into the Li 2 S structure to form a Li 2−2x Mg x S solid solution with the limitation at x of nearly 0.1. In fact, the effect of Mg 2+ doping on Li 2 S ionic conductivity was also investigated by Lorger et al, but only a slight improvement of the ionic conductivity was observed [12]. Takeuchi et al prepared Li 2 S-FeS nanocomposites with different molar ratios and applied them to all-solid-state batteries [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the electronic and ionic conductivity of sulfur and Li 2 S/Li 2 S 2 are poor, thus uncontrolled deposition of solid active materials during charging‐discharging process would easily generate “dead sulfur”, which cannot participate in the following redox reaction . Fourth, thick SEI layer and Li dendrite growing on the lithium surface, as well as other problems such as liquid electrolyte exhausting would further exacerbate the cycle life or even lead to considerable security risks …”
Section: Introductionmentioning
confidence: 99%